أهل الذِمَّة في المصادر الاباضية المغربية Dhimmis in Maghrebin Ibadhi sources - الحاج عيسى, إلياس بن عمر; عبد الحق, شرف (مجلة العبر للدراسات التاريخية و الاثرية في شمال افريقيا, 2023)
الملخص باللغة العربية: ينقسم الحضور الذمّي في المصادر الاباضية المغربية إلى قسمين، قسم يتعلق بمصادر التنظير والتأصيل العقدي والفقهي، وفيها إيضاح لعلاقة المسلم "الإباضي" بالذمّي سواءً كان نصرانيا أو يهوديا أو مجوسيا، وهذه المصادر تهتم بالجوانب العقدية والفقهية من منظور إباضي، وفيها تأكيد على موقف الإسلام من أهل الذمّة في المجتمع المسلم، وهي آراء ومواقف تتواقف كليا مع التفسيرات السنيّة حول الموضوع. وهي ترى أنه يحلّ من أهل الكتاب: الجزية ونكاح الحرائر وأكل ذبائحهم. وقد فصّلت مصادر العقيدة والكلام الاباضية في سياق حديثها عن الفِرَق، حول الموضوع، منها، كتاب الموجز لأبي عمار عبد الكافي التناوتي الوارجلاني، وكتاب أصول الدين لِـ: تِبْغُورينْ بن داود الـمَلْشُوطي، ورسائل في الفِرَق لأبي عمرو عثمان بن خليفة السُّوفي الـمَارْغَني. بينما القسم الآخر، خاص بمصادر السير والتراجم والمسائل، وفيها نماذج من الواقع المغربي عن صورة الذمّيين في المجال الإباضي المغربي. وعادة ما كان لفظ "الذمي" مرادفاً للفظ "اليهودي"، ذلك أن اليهود كانوا أكثر حضوراً وتأقلما وتأثيراً، مقارنة بالنصارى. سنسعى من خلال هذه الورقة البحثية وصف وتحليل وتفسير ظاهرة الذمّي في الفضاء الإباضي المغربي، من خلال مصادرهم. Abstract: through this paper, we will seek to describe, analyze and explain the phenomenon of “dhimmis” in the Maghrebin Ibadhi domain, bu dealing with their sources. The dhimmi presence in Ibadhi Maghrebin sources is divided into two parts: A section related to the sources of jurisprudence with an explanation of the good relationship and an affirmation of the position of Islam towards the “dhimmis” in the Muslim community, where opinions and positions are completely compatible with the Sunni interpretations on the subject, whether he is a Christian, a Jew, or a Magus. These sources consider that it is permissible for both Christians and Jews: the tribute, the marriage, and the eating of their sacrifices. It have detailed the Ibadi belief and speech on the subject, including, the book Al-Mujaz by Abu Ammar Abdul Kafi Al-Tanaouti Al-Warajlani, and the book “Osoul al-Din” by Tibgurin bin Dawood al-Malshooti, and the letters in the sects for Abu Amr Othman bin Khalifa al-Soufi al-Marghani While the other section is concerned with the sources of biographies, translations, and issues, and it contains examples from the Maghrebin reality of the image of the “dhimmis” in the Maghrebin Ibadhi field. The term "dhimmi" was usually synonymous with the term "Jew", because the Jews were more present, adaptive and influential, compared to the Christians.
Keywords: Ibadisme – minorités